1987
DOI: 10.1080/02681218780000041
|View full text |Cite
|
Sign up to set email alerts
|

The lipid composition and permeability to azole of an azole- and polyene-resistant mutant ofCandida albicans

Abstract: Candida albicans 6.4, which is resistant to both polyene and azole groups of antifungal antibiotics, has a larger lipid content and lower polar lipid to neutral lipid ratio compared with other strains that are sensitive or resistant only to azoles. C. albicans 6.4 contains a relatively greater proportion of triacylglycerol in its neutral lipid in the exponential phase of batch culture compared with other strains, but, unlike them, does not accumulate triacylglycerols or any other stored lipid in the stationary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
40
1

Year Published

1994
1994
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(46 citation statements)
references
References 23 publications
5
40
1
Order By: Relevance
“…A similar ergosterol content has been described in a strain of A. fumigatus which is susceptible to amphotericin B in vivo [23,24]. Polyene antifungal resistance has previously been attributed to lesions in the ergosterol biosynthetic pathway in clinical isolates of Candida albicans [22,25,26] and Cryptococcus neoformans [27] and in laboratory mutants of C. albicans [22,28], A. fennelliae [29] and of a protozoan, Leishmania donovani [30]. Nevertheless, amphotericin B resistance has also been reported in C. albicans [31], Cr.…”
Section: Discussionmentioning
confidence: 75%
“…A similar ergosterol content has been described in a strain of A. fumigatus which is susceptible to amphotericin B in vivo [23,24]. Polyene antifungal resistance has previously been attributed to lesions in the ergosterol biosynthetic pathway in clinical isolates of Candida albicans [22,25,26] and Cryptococcus neoformans [27] and in laboratory mutants of C. albicans [22,28], A. fennelliae [29] and of a protozoan, Leishmania donovani [30]. Nevertheless, amphotericin B resistance has also been reported in C. albicans [31], Cr.…”
Section: Discussionmentioning
confidence: 75%
“…PI has been shown to contribute to antifungal resistance (Abu-Elteen & Whittaker, 1997-1998Hitchcock et al, 1987), biosynthesis and localization of GPI-anchored proteins, germination (Koul et al, 1995) and host pathogenesis (Reynolds, 2009). Additionally, PI metabolism is intricately tied to biosynthesis of yeast sphingolipids, which are a major constituent of membrane-localized lipid rafts.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have revealed that biofilm formation by C. albicans is associated with differential expression of genes and proteins involved in the synthesis of membrane lipids (Lattif et al, 2008;Yeater et al, 2007), and that alteration in the sterol composition is linked to increased azole resistance of C. albicans biofilms (Mukherjee et al, 2003). Additionally, phosphatidylinositol (PI), a key yeast phospholipid, has been shown to contribute to antifungal resistance (Abu-Elteen & Whittaker, 1997-1998Hitchcock et al, 1987) and pathogenesis (Reynolds, 2009). PI is a precursor for the biosynthesis of glycosylinositol phosphorylceramides (GIPCs), the yeast-specific sphingolipid constituents of membrane-localized lipid rafts.…”
Section: Introductionmentioning
confidence: 99%
“…Thus far, two mechanisms for the reduced susceptibility of C. albicans to azole antifungal agents have been described. One is due to changes in the membrane sterol composition which cause a reduced level of permeability of the C. albicans membrane to the drugs; the second is due to a mutation of sterol 14a-demethylase, a cytochrome P450 enzyme, that results in decreased binding affinity for the azole drugs (6,7,14,16 …”
Section: Discussionmentioning
confidence: 99%